If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + y)(5y + 3) = 0 Reorder the terms: (7 + y)(3 + 5y) = 0 Multiply (7 + y) * (3 + 5y) (7(3 + 5y) + y(3 + 5y)) = 0 ((3 * 7 + 5y * 7) + y(3 + 5y)) = 0 ((21 + 35y) + y(3 + 5y)) = 0 (21 + 35y + (3 * y + 5y * y)) = 0 (21 + 35y + (3y + 5y2)) = 0 Combine like terms: 35y + 3y = 38y (21 + 38y + 5y2) = 0 Solving 21 + 38y + 5y2 = 0 Solving for variable 'y'. Factor a trinomial. (7 + y)(3 + 5y) = 0Subproblem 1
Set the factor '(7 + y)' equal to zero and attempt to solve: Simplifying 7 + y = 0 Solving 7 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + y = 0 + -7 y = 0 + -7 Combine like terms: 0 + -7 = -7 y = -7 Simplifying y = -7Subproblem 2
Set the factor '(3 + 5y)' equal to zero and attempt to solve: Simplifying 3 + 5y = 0 Solving 3 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5y = 0 + -3 5y = 0 + -3 Combine like terms: 0 + -3 = -3 5y = -3 Divide each side by '5'. y = -0.6 Simplifying y = -0.6Solution
y = {-7, -0.6}
| 11x+35+35=180 | | 3p-42=31 | | 1-0.4=2 | | 18x-4+4x=172 | | 8w+12-6w=5(w+3)-2w | | a^2-16a+63=0 | | .5x+4=-6 | | -1+4/25=-1 | | 4x*2c-4+4c=0 | | t(p)=(ln(p/25))/.12 | | 2z+8-9=-30.5 | | m+3-(2)=7 | | .6n+4=18 | | 8x=x-2 | | (-9x-3).2/3 | | r^2-16r+15=0 | | 34x+3+96+59x+75=360 | | 9k+3=12k | | 130+48+14x=360 | | 2w+7=16 | | 42j+19j-18=28 | | 9x-3+30=90 | | n^2-10n-39=0 | | (2x-1)(x+8)=2x^2+15x-8 | | 5sin^2a-5sin^4a=5cos^2a-5cos^4a | | 8+14x-7=7x+56-4x | | Z-7=1+2Z | | 6t=-21 | | 2Y+9=10Y | | 6x+9=rx+t | | x(90-x)=18 | | -22.5=7k-5.5k |